Excessive Iodine Enabled Ultrathin Inorganic Perovskite Growth at the Liquid‐Air Interface. Issue 19 (23rd March 2023) - Yuan, Jiaxiao; Zhang, Xiaomin; Zhou, Dawei; Ge, Feixiang; Zhong, Jingxian; Zhao, Sihan; Ou, Zhenwei; Zhan, Guixiang; Zhang, Xu; Li, Congzhou; Tang, Jin; Bai, Qi; et al.
Abstract: The liquid‐air interface offers a platform for the in‐plane growth of free‐standing materials. However, it is rarely used for inorganic perovskites and ultrathin non‐layered perovskites. Herein the liquid‐air interfacial synthesis of inorganic perovskite nanosheets (Cs3 Bi2 I9, Cs3 Sb2 I9 ) is achieved simply by drop‐casting the precursor solution with only the addition of iodine. The products are inaccessible without iodine addition. The thickness and lateral size of these nanosheets can be adjusted through the iodine concentration. The high volatility of the iodine spontaneously drives precursors that normally stay in the liquid to the liquid‐air interface. The iodine also repairs in situ iodine vacancies during perovskite growth, giving enhanced optical and optoelectronic properties. The liquid‐air interfacial growth of ultrathin perovskites provides multi‐degree‐of‐freedom for constructing perovskite‐based heterostructures and devices at atomic scale. Abstract : Ultrathin inorganic perovskite nanosheets are prepared by liquid‐air interfacial synthesis by adding only iodine into the precursor solution. The thickness, lateral size, defects, optical and optoelectronic properties of these freestanding materials are optimized by simply adjusting the iodine concentration of the solution.